Audible noise reduction in the high frequency injection based sensorless torque control for EPS applications - Jiang, Hui (2012)
This thesis has investigated the reduction of audible noise in low speed sensorless controlled drives for automotive electrical power steering (EPS) applications. The specific methods considered employ saliency tracking high frequency (hf) voltage injection in the machine's estimated d axis. In terms of the audible noise reduction, a novel random sinusoidal hf injection sensorless method has been proposed. The perceived audible noise due to the hf injection can be reduced by randomly distributing the injection frequencies around a centre frequency, such that it is perceived as a background hiss rather than the fixed tone heard with fixed hf injection methods. By analysing the A-weighting scales used to classify human perception of audible noise and frequency analysis of the recorded noise, an injection frequency of (lS00±328) Hz is found to have the lowest audible noise level compared to other random frequencies and other fixed frequencies methods. A 10 kHz square wave hf injection sensorless method has also been implemented. The frequency analysis of the recorded audible noise indicates that it also may be lower than for the fixed hf sinusoidal injection. In terms of control performance, sensorless torque control for these methods has been achieved from zero speed to ±240rpm with up to ±60A load (about 63% rated load). Similar position estimate quality has been demonstrated. Dynamic performance for a step change in torque current demand and for a speed reversal has been performed, and the random injection method with (1S00±328) Hz frequency has been found to be able to control a step change in torque demand current of 50A whilst for the 10kHz square wave injection method only a 40A step change can be achieved. On the other hand, the average position error after the speed transient has settled is less for the 10 kHz square ewave injection than for the random injection.